Effect of Digital Strategic Partnerships on Financial Performance of Commercial Banks in Kenya - Achieng, Okongo Fiona; Kabisani, Francis Mutegi (Journal of Consumer Studies and Applied Marketing, 2025)
The study aimed to evaluate the impact of digital strategic partnerships on the financial performance of commercial banks in Kenya. This comes amid declining financial performance among most banks in the country, and a changing market landscape characterised by disruptions in the financial market. While available empirical evidence suggests that the essence of digital strategic partnerships lies in stimulating the performance of modern enterprises, there remains scant evidence in the case of commercial banks, particularly in Kenya. This motivated the study to assess the extent to which commercial banks in Kenya have embraced digital strategic partnerships and how this has influenced their financial performance. The study was grounded in the resource-based view theory. The study employed a descriptive research design, surveying 112 respondents from 39 commercial banks in Kenya. A structured questionnaire was used to collect data, which was analysed using descriptive and inferential statistics. The findings revealed that most of the surveyed commercial banks had embraced digital strategic partnerships, especially with fintech companies. It was also established that a significant and positive relationship exists between digital strategic partnerships and the financial performance of commercial banks in Kenya. The study concluded that the banking industry in Kenya was steadily focusing on digitalising its processes, thus enhancing digital strategic partnerships was a norm in most banks. It is recommended that while most banks have embraced digital strategic partnerships, institutionalising these partnerships is essential to make them more profound and long-lasting, thereby contributing to the continued competitiveness of the banks. Furthermore, banks need to take a step further and invest in digital infrastructure and skills, as well as enter into digital strategic partnerships that incorporate at least the basics, to enhance their competitive advantage in these partnerships.